GE_GERICHTE C/17967/2011 vom 17. März 2014 - GE Cour de justice (2014)
ACTION EN CONSTATATION; INTERPRÉTATION(SENS GÉNÉRAL); TRANSFERT DE BAIL; PROLONGATION | CO.263; CO.255.1; CO.272; CPC.317.2; CO.272b.1